Anesthesia protocols in laboratory animals used for scientific purposes - Cicero, Luca; Fazzotta, Salvatore; Palumbo, Vincenzo Davide; Cassata, Giovanni; Lo Monte, Attilio Ignazio (Acta Biomedica Atenei Parmensis, 2018)
Background: A suitable, effective and free of complications anesthetic protocol is very important in experimental studies on animal models since it could bias the outcome of a trial. To date there is no universally accepted protocol for induction, maintenance and recovery from anesthesia. The endotracheal intubation with the use of inhalation anesthesia is used very especially in the from of large size laboratory animals, because it is a secure and easy control mode. However, it is not common for small laboratory animals because of the high technical skills required. Aim: The aim of this paper is a review of the main methods of induction of anesthesia in laboratory animals. Materials and methods: We performed an electronic search of MEDLINE (PubMed interface), ISI Web of Science and Scopus using the keywords “anesthesia” and “animal (s)” or “protocol (s)” or “surgery”, without the data or the language restriction. We consider only the most common laboratory animals (rats, mice, rabbits, pigs). We identify all the scientific articles that refer to the use of anesthetics for studies on laboratory animals in all areas: experimental surgery, CT, MRI, PET. All documents identified the search criteria are subject to review only by identifying relevant studies. Conclusions: There is a strong need for application of existing guidelines for research on experimental animals; specific guidelines for anesthesia and euthanasia should be considered and reported in future studies to ensure comparability and quality of animal experiments.